The Importance of Derivatizing Reagent in Chromatography Applications for Biogenic Amine Detection in Food and Beverages - Muhammad Abdurrahman, Munir; Khairiah Haji, Badri (Hindawi Publishing, 2020)
Biogenic amines (BA) are chemical compounds formed in foods that contain protein, allowing the foods to undergo a bacterial degradation process. Biogenic amines are labeled as toxic food because its consumption exceeding the FDA regulation (50 mg/kg) can be harmful to humans. Some countries also have regulations that prohibit the consumption of biogenic amines in high concentrations, especially histamine. The chromatography methods generally applied by researchers are liquid chromatography (LC) and gas chromatography (GC), where the use of a derivatization reagent is necessary to increase their sensitivity. This review is based on past and present studies about biogenic amine detection related to food samples. The rationale of this study is also to provide data on the comparison of the analytical approaches between LC and GC methods. Furthermore, the various approaches of biogenic amine determination and the most applied analytical methods have been reviewed.